Sexual Dysfunction in Patients with Alcohol and Opioid Dependence - Grover, Sandeep; Mattoo, Surendra K.; Pendharkar, Shreyas; Kandappan, Venkatesh (Indian journal of psychological medicine, 2014)
There are limited numbers of studies which have evaluated the sexual dysfunction (SD) in patients with alcohol and opioids dependence. This article reviews the existing literature. Electronic searches were carried out using the PubMed, Google Scholar, and ScienceDirect to locate the relevant literature. Subjects addicted to heroin or on methadone maintenance treatment (MMT) or buprenorphine maintenance treatment (BMT) show higher rates of SD in comparison to the general population. SD rates have ranged 34-85% for heroin addicts, 14-81% for MMT, 36-83% for BMT, and 90% for naltrexone maintenance. The rates of SD in alcohol-dependent population have ranged 40-95.2%, with rates being consistently much higher in alcohol-dependent population than in the healthy controls or social drinkers. The common SDs reported have been erectile dysfunction followed by premature ejaculation, retarded ejaculation and decreased sexual desire among men, and dyspareunia and vaginal dryness among women. This review suggests that long-term use of alcohol and opioids are associated with SD in almost all domains of sexual functioning. There is a need to increase the awareness of clinicians about this association as many times SD in patients with substance abuse lead to poor treatment compliance and relapse. Further, there is a need to carry out more number of studies to understand the relationship in a better way.